Teacher Strategies in Developing Children's Social-Emotional Skills at RA Al-Khairat Skep, Ternate City - H Haryati; Khumairah Imran; Adiyana Adam (Manunggal Halim Jaya, 2026)
This study aims to describe the strategies used by teachers in developing the social-emotional abilities of early childhood at RA Al-Khairat Skep. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included teachers and students at RA Al-Khairat. The results of the study indicate that teachers’ strategies in children's social-emotional development are carried out through play-based learning, positive behavioral habits, and empathetic emotional approaches. These strategies contribute to improving children's abilities in social interaction, cooperation, managing emotions, and appropriately expressing feelings. Supporting factors in the implementation of strategies include teacher commitment and a conducive school environment, while inhibiting factors include limited time, learning facilities, and differences in children's family backgrounds. This study emphasizes the importance of teachers’ role in creating a safe learning environment and supporting the social-emotional development of early childhood.